Note by Professor Marshall and Reply by Laughlin - Marshall, A.; Laughlin, J. L. (Quarterly Journal of Economics, 1887)
Alfred Marshall, J. Laurence Laughlin; Note by Professor Marshall and Reply by Laughlin, The Quarterly Journal of Economics, Volume 1, Issue 3, 1 April 1887, Pa